Preliminary Study of Treatment of Spent Test Tubes Used for Blood Tests by Acidic Electrolyzed Water - Tateda, Masafumi; Daito, Tomoya; Kim, Youngchul; Athapattu, B.C. Liyanage (IntechOpen, 2011)
None